2019
DOI: 10.1177/0271678x19872564
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cerebral blood flow in adults by contrast-enhanced near-infrared spectroscopy: Validation against MRI

Abstract: The purpose of this study was to assess the accuracy of absolute cerebral blood flow (CBF) measurements obtained by dynamic contrast-enhanced (DCE) near-infrared spectroscopy (NIRS) using indocyanine green as a perfusion contrast agent. For validation, CBF was measured independently using the MRI perfusion method arterial spin labeling (ASL). Data were acquired at two sites and under two flow conditions (normocapnia and hypercapnia). Depth sensitivity was enhanced using time-resolved detection, which was demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 56 publications
4
59
0
Order By: Relevance
“…, whereas average thicknesses of the scalp (5 mm) and skull (7 mm) layers were obtained from a previous study. 31 It should be noted that the assumed optical properties were similar to reconstructed values presented in Sec. 3 and from previous studies.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…, whereas average thicknesses of the scalp (5 mm) and skull (7 mm) layers were obtained from a previous study. 31 It should be noted that the assumed optical properties were similar to reconstructed values presented in Sec. 3 and from previous studies.…”
Section: Discussionsupporting
confidence: 61%
“…The fitting parameters were the absorption coefficient (μ a ), the reduced scattering coefficient (μ 0 s ), and an amplitude factor. Next, the time series for each of the three moments was converted into the corresponding absorption changes Δμ a;i ðλÞ by sensitivity analysis: 31,54 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 1 1 6 ; 2 4 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, the opticalderived CBF has physical units (i.e., cm 2 /s) rather than the more usual clinical units (i.e., ml/100 g of tissue/min). Some authors have proposed the use of an indocyanine-green (ICG) bolus to recover absolute CBF from the optical signal, which may be used to convert the continuous CBF index from DCS to the absolute clinical units (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…However, MR demands that subjects are immobile for a longer period and has several contra-indications, such as metal implants. Recently, it was reported that dynamic contrast-enhanced near-infrared spectroscopy could assess CBF at the bedside, 5 which compensates for the disadvantages of MR, but this technique still needs to be validated.…”
Section: Introduction Background and Rationalementioning
confidence: 99%